New Method of Classic Laryngeal Mask Air Way Insertion - Jasim M. Salman (New Advances in Medicine and Medical Science Vol. 6, 2023)
The present study was carried out to validate the new method for correct anatomic placement of the LMA and to compare it with the standard technique. Laryngeal mask airway (LMA) is a supraglottic airway device used to control the airway during the administration of anesthesia in the operating room and for emergency airway management. This study was done in Basrah University Medical Center from 1st January 2019 to 31st December 2019. Patients were randomly assigned and categorized into two groups; Group I – the study group, and Group II – the standard (control) group. Results were expressed as frequencies or means ± standard deviations. Frequencies or means were compared using X2 and t-test, respectively. Study conducted a new technique in which the device is inserted easily without digital manipulation during insertion. It will be appropriate for the anesthesiologists and medical personnel who use LMA as there is less risk of contamination or trauma to their fingers. Three hundred and ninety-seven (397) participants were enrolled in this study with a mean age of 35.7 ± 14 y. Of those, 154 (38.8%) were males. The new method showed higher sensitivity and accuracy rate (97.4%, 95.9%, respectively) compared to the standard method. In comparison to the conventional method of insertion, the new method is a suitable technique that improved the ease of LMA insertion and successfully implanted the device in a shorter amount of time without complications. The study recommends this technique to be used in anesthetic practice as a sole method, or as an alternative technique, whenever there is a difficulty.